Developing ethical managers for future business roles: a qualitative study of the efficacy of "Stand-Alone" and "Embedded" University "Ethics" courses. Issue 2 (20th April 2020) - Coldwell, David Alastair; Venter, Robert; Nkomo, Emmanuel
Abstract : Purpose: While the problem of unethical leadership is undoubtedly a global one, the urgency of generating ethical leadership to advance the development of Africa has never been more evident than it is today. The challenge for higher education in developing ethical leaders is of core importance, as it is responsible for providing the main recruiting ground of business leaders. The current paper reports findings of a qualitative study of postgraduate students' ethical development at the end of courses in business ethics aimed to enhance moral reasoning and ethical decision-making. The paper aims to ascertain whether stand-alone ethics courses are more effective than integrated ones in achieving academic ethical competency. Design/methodology/approach: The study adopts an idiographic approach which aims at eliciting individual student subjective perceptions of the effects of the direct and indirect courses of ethical instruction on their moral reasoning and ethical practice. The research design broadly follows Mill's (2017) method of difference. Findings: Findings indicate perceived differences in the relative effectiveness of stand-alone and embedded ethics courses among students but also show that most students hold positive overall evaluations of the effectiveness of the both types of ethics instruction. Research limitations/implications: Limitations to the study include that it is cross-sectional, involves a small sample of postgraduate students and is restricted to two management courses at one institution of higher learning. Furthermore, while Mill (2017) provides a useful research design in this context, it is not able to indicate causality, as there are other possible unidentified "third variables" that may be the actual cause of student differences between embedded and stand-alone ethics courses. The study is not able to show the durability and transfer of ethical competencies into students' later working lives. Practical implications: The study provides a useful practical educational contribution to the extant knowledge in the field in that it suggests that ethical courses aimed at giving students a moral reasoning "toolkit" for ethical decision-making are more effective when delivered in the stand-alone format, whereas practical decision-making skills are best honed by embedded business ethics courses. Social implications: The problem of corruption in business and politics in South Africa is widely documented and has been regarded as responsible for creating a serious developmental drag on the alleviation of poverty and quality of lives of the majority of people in the country. The moral/ethical competency and behavior of future business leaders is partly the responsibility of institutions of higher learning. The study aims to find the most effective means of imparting moral awareness in postgraduate students who are likely to take up business leadership positions in their future careers. Originality/value: The study provides useful contribution to the extant knowledge in the field in the African context in that it suggests that ethical courses aimed at giving students a moral reasoning "toolkit" for ethical decision-making are more effective when delivered in the stand-alone format, whereas practical decision-making skills are best honed by embedded business ethics courses.